Persepsi Peserta terhadap Penggunaan Media Kahoot Sebagai Penutup Pembelajaran, Studi Kasus: Mata Pelatihan Akuntabilitas Latsar CPNS Golongan III Tahun 2020 - Arisman, Arisman; Supandi, Achmad (Jurnal Widya Climago, 2024)
The use of media tools in the learning process needs to be done in an effort to measure the learning achievements of the training participants. Kahoot as a popular application can be used to support the learning process, one of which is a closing lesson. A review of learning using the Kahoot in the course of the 2020 Pelatihan Dasar CPNS in Accountability Material has been carried out. The results show that in general participants are helped in getting an overview of learning (97% of participants), increasing enthusiasm and motivation to learn (98%), and stimulating curiosity. Regarding the material (96%), respondents also stated that they were happy to use kahoot (> 80%), as many as 98% of respondents had the perception that Kahoot played a role in fostering critical thinking skills, thinking skills and making quick decisions.